In Hutchings and Taubes lecture note on Seiberg-Witten equation HERE, above equation (4.20) the authors claim that there is a version of Weitzenbock formula reads (where $\beta \in \Omega^{0,2}(M, E)$, M is a symplectic manifold with compatible $J$, $E$ is a line bundle with $U(1)$ connection $a$)

\begin{equation} \int {{{\left| {\bar \partial _a^*\beta } \right|}^2}} = \frac{1}{2}\int {\left( {{{\left| {\nabla _a^*\beta } \right|}^2} - i\left\langle {\omega ,{F_a}} \right\rangle {{\left| \beta \right|}^2}} \right)} \end{equation}

I try to prove it, by first guessing that it might come from something like a Kahler identity \begin{equation} {{\bar \partial }_a}\bar \partial _a^*\beta = \frac{1}{2}{\nabla _a}\nabla _a^*\beta + \left( {...} \right) \end{equation} and try to figure out if the ... matches the formula in the note. But I could not reproduce the result: the ... I got is of the form $\Lambda \left( {F_a^{2,0} \wedge \beta } \right)$, where $\Lambda = (\omega\wedge)^*$, and a (2,0)-piece of $F$ rather than a (1,1) piece shows up.

So I wonder how to prove the Weitzenbock formula above? Any reference is welcome; I google for a while but may be I am not looking at the write place.

  • $\begingroup$ Does this not follow from equation (4.14) on the previous page, which is Lemma 6.1.7 of Donaldson-Kronheimer? $\endgroup$ – Henry T. Horton May 8 '14 at 20:54
  • $\begingroup$ @HenryT.Horton: (4.14) is for $\Omega^{0,0}(E)$. I managed to prove (4.14), but not the one I am confused about. $\endgroup$ – Lelouch May 9 '14 at 0:52
  • $\begingroup$ Have a look at section 1.4.2 in www3.nd.edu/~lnicolae/swnotes.pdf $\endgroup$ – Liviu Nicolaescu Jun 5 '14 at 13:42

Perhaps this is the proof, at least for the Kahler case. I use complex coordinate system: \begin{equation} \beta = \frac{1}{{2!}}{\beta _{\bar \mu \bar \nu }}d{{\bar z}^{\bar \mu }} \wedge d{{\bar z}^{\bar \nu }} = {\beta _{\bar 1\bar 2}}d{{\bar z}^{\overset{\lower0.5em\hbox{$\smash{\scriptscriptstyle\smile}$}}{1} }} \wedge d{{\bar z}^{\bar 2}} \end{equation}

Then \begin{equation} {{\bar \partial }^*}\beta = - {\nabla ^{\bar \mu }}{\beta _{\bar \mu \bar \nu }}d{{\bar z}^{\bar \nu }} \to \bar \partial {{\bar \partial }^*}\beta = - {\nabla _{\bar \lambda }}{\nabla ^{\bar \mu }}{\beta _{\bar \mu \bar \nu }}d{{\bar z}^{\bar \lambda }} \wedge d{z^{\bar \nu }} \end{equation}

Commuting the covariant derivatives, one gets the curvature and another second order derivative: \begin{equation} \bar \partial {{\bar \partial }^*}\beta = - \bar \partial \left( {{\nabla ^{\bar \mu }}{\beta _{\bar \mu \bar \nu }}} \right)d{z^{\bar \nu }} = {F_{\bar \lambda }}^{\bar \mu }{\beta _{\bar \mu \bar \nu }}d{{\bar z}^{\bar \lambda }} \wedge d{z^{\bar \nu }} - \frac{1}{2}{\nabla ^{\bar \mu }}{\nabla _{\bar \mu }}{\beta _{\bar \nu \bar \lambda }}d{{\bar z}^{\bar \lambda }} \wedge d{z^{\bar \nu }} \end{equation}

In passing, one needs to use the fact that we are sitting on a 4-manifold, and therefore $\bar \partial \beta = 0$, namely \begin{equation} {\nabla ^{\bar \mu }}{\nabla _{\bar \lambda }}{\beta _{\bar \mu \bar \nu }}d{{\bar z}^{\bar \lambda }} \wedge d{z^{\bar \nu }} = - \frac{1}{2}{\nabla ^{\bar \mu }}{\nabla _{\bar \mu }}{\beta _{\bar \nu \bar \lambda }}d{{\bar z}^{\bar \lambda }} \wedge d{z^{\bar \nu }} \end{equation}

Finally,${F_{\bar \lambda }}^{\bar \mu }{\beta _{\bar \mu \bar \nu }}d{{\bar z}^{\bar \lambda }} \wedge d{z^{\bar \nu }} = \left( {{F_{\bar 1}}^{\bar 1} + {F_{\bar 2}}^{\bar 2}} \right)\beta \sim\left\langle {\omega ,F} \right\rangle \beta $

So up to some convention of $i$, the formula is obtained.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.